Calcium transfer process of cement paste for ettringite formation under different sulfate concentrations. (19th September 2022) - Hou, Wei; Liu, Jing; Liu, Zanqun; He, Fuqiang; Zhu, Jiahui; Cui, Yu; Jinyang, Wu
Highlights: Portlandite was firstly consumed to provide calcium for ettringite formation and the decalcification of C-S-H will not take place until all the portlandite was fully consumed. When the pH is 10.8 and 11.8, blending with metakaolin can inhibit the sulfate attack, however, it will accelerate the sulfate attack at the condition of pH is 12.6. Gypsum only exists as a transition phase in the early corrosion stage, and then will immediately react with the aluminum phase to form ettringite. Abstract: Incorporating metakaolin in the concrete preparation process has great significance for reducing CO2 emissions. More ettringite will be formed when cement blending with metakaolin subjected to sulfate attack. The calcium in ettringite formed in the course of sulfate attack may be sourced from either portlandite or C-S-H gel. A better understanding of ettringite formation can further disclose the real world of sulfate attack on concrete. In this paper, the cement paste slices with a size of Ø20 mm × 3 mm (ignoring the influence of penetration) were immersed in 1000 mg/L, 10000 mg/L, and 35000 mg/L Na2 SO4 solutions with different pH values of 10.8 ± 0.1, 11.8 ± 0.1, 12.6 ± 0.1, respectively. According to the micro-analysis results of X-Ray diffraction (XRD), backscattered electron and energy dispersive scanning (BSE-EDS) and 29 Si nuclear magnetic resonance ( 29 Si NMR), results confirmed that the decalcification process of hydration products was that the portlandite was firstly consumed to provide calcium for ettringite formation and the decalcification of C-S-H will not take place until all the portlandite was fully consumed. As a result, the Ca/Si ratio and the calcium content in the interlayer of the C-S-H gel decreased.